Socio-hydrology: the pros and cons of a new interdisciplinary field of research - Хільчевський, Валентин Кирилович (Київський національний університет імені Тараса Шевченка, 2021)
The purpose of the survey study was to characterize the state of affairs in sociohydrology, the concept of which began to actively gain positions in the world in the early 2000s. The publication of 2012 by M. Sivapalan et al. is considered to be the reference in the appearance of a statement about a certain systematic design of sociohydrology. In it, the authors defined sociohydrology as a new science that studies dynamic interactions and feedbacks between water and humans. A significant number of researchers have taken up the idea of new science. Analysis of publications in international journals on topics related to sociohydrology showed that in scientific periodicals during 2012–2020. About 180 articles were published, cited about 4000 times according to the Web of Science. The main content of research in the field of sociohydrology boils down to three aspects: compromise in the interconnected system “man – water”; interests in water resources management; virtual research of water in a connected system “man – water”. However, the scientific hydrological community did not unanimously accept the idea of the emergence of new science. Some hydrological scientists believe that sociohydrology is a field of hydrology. They note that there is a tendency in sociohydrology publications to borrow fashionable syntaxes and popular concepts from other fields, but it does not take into account the previous and current advances in the study of human-water related systems, which have already been obtained in hydrology. As a conclusion to this review article on sociohydrology, one can support the opinion of K. Madani and M. Shafiee-Jood, who note that the valuable contribution of sociohydrologists lies not in their “new science”, models, ambitious statements, but in their persistence and reminding hydrologists of the need to take into account the human factor. With regard to the Ukrainian realities in the context of sociohydrology, or studies of the “man – water” system, practical and scientific aspects can be noted: a) practical – after the signing of the Ukraine-EU Association Agreement (2014), a system of integrated water resources management is being implemented in Ukraine by implementing the provisions of the EU Water Framework Directive into the practice of water relations; by 2024, river basin management plans should be developed, which to a certain extent take into account the interrelated manifestations of the linked system “man – water”; b) scientific – Ukrainian scientists need to use the world experience in applying research methods to integrate hydrological and socio-economic aspects of water resources planning, given that there are social, economic and hydrological subsystems in socio-hydrological systems that are causally related; such an approach would allow, for example, to give a clear answer to the question about the significance of the Dnieper cascade of reservoirs for the country.

Метою дослідження було охарактеризувати стан справ у соціогідрології, концепція якої почала активно завойовувати позиції у світі з початку 2000-х рр. За відлік про певне системне оформлення соціогідрології прийнято вважати публікацію 2012 р. M. Sivapalan та ін. У ній було визначено соціогідрологію як нову науку, що вивчає динамічні взаємодії та зворотний зв’язок між водою і людиною: історичне вивчення взаємодії між гідрологічними й соціальними процесами; порівняльний аналіз коеволюції та самоорганізації людини і водних систем у різних культурах; процесне моделювання взаємодії людини та водних систем. Значною кількістю дослідників підхоплено ідею нової науки. На прикладі аналізу публікацій у міжнародних журналах із тематики, що належить до соціогідрології, показано, що в науковій періодиці протягом 2012–2020 рр. вийшло близько 180 статей, які процитовані близько 4000 разів за даними Web of Science. Основний зміст досліджень у галузі соціогідрологіі зводиться до трьох аспектів: компроміс у зв’язаній системі “людина – вода”; інтереси в управлінні водними ресурсами; віртуальні дослідження води у зв’язаній системі “людина – вода”. Показано, що наукова гідрологічна громадськість не одностайно сприйняла ідею виникнення нової науки. Частина вчених-гідрологів уважає, що соціогідрологія є галуззю гідрології. Вони зауважують, що в публікаціях із соціогідрології помітна тенденція до запозичення модних синтаксисів і популярних концепцій із інших сфер, але при цьому не беруться до уваги попередні й сьогоднішні надбання у сфері дослідження пов’язаних систем “людина – вода”, які вже отримані в гідрології. Однак опоненти наголошують, що цінний унесок соціогідрологів полягає в їхній наполегливості у нагадуванні гідрологам про необхідність урахування людського чинника в дослідженнях гідрологічних систем. Наголошено, що українським ученим необхідно використовувати світовий досвід застосовування методів дослідження з інтеграції гідрологічних і соціально-економічних аспектів планування водних ресурсів, ураховуючи, що в соціально-гідрологічних системах існують соціальні, економічні та гідрологічні підсистеми, які причинно пов’язані. Такий підхід дозволив би, наприклад, дати чітку відповідь на питання про роль і значення Дніпровського каскаду та й водосховищ узагалі для країни.Ключові слова: соціогідрологія, система “людина – вода”, соціогідрологічне моделювання, інтегроване управління водними ресурсами, водосховища, гідрологія.
Соціогідрологія: плюси і мінуси нової міждисциплінарної області досліджень
Anderson, R.E., Beard, L.S., 2010. Geology of the Lake Mead region. An overview: Miocene Tectonics of the Lake Mead Region, Central Basin and Range. Geological Society of America. DOI:10.1130/2010.2463(01). Baldassarre, G., Nohrstedt, D., Mård, J., Burchardt, S., Albin, C., Bondesson, S., Breinl, K., Deegan, F.M., Fuentes, D., 2018. An Integrative Research Framework to Unravel the Interplay of Natural Hazards and Vulnerabilities. Earth’s Future, 6(3), 305–310. DOI: 10.1002/2017EF000764 Blair, P., Buytaert, W., 2016. Socio-hydrological modelling: a review asking “why, what and how?”. Hydrology and Earth System Sciences, 20(1), 443–478. DOI: 10.5194/hess-20-443-2016 Di Baldassarre, G., Viglione, A., Carr, G., Kuil, L., Salinas J.L., Blöschl, G., 2013. Socio-hydrology: conceptualising human-flood interactions. Hydrology and Earth System Sciences, 17(8), 3295–3303. DOI:10.5194/hess-17-3295- 2013.5 Di Baldassarre, G., Wanders, N., AghaKouchak, A., Kuil, L., Rangecroft, S., Veldkamp, T. I. E., Garcia, M., van Oel, P. R., Breinl, K., 2018. Water shortages worsened by reservoir effects. Nature Sustainability, 1(11), 617- 622. DOI: 10.1038/s41893-018-0159-0 Falkenmark, M., 1979. Main problems of water use and transfer of technology. GeoJournal, 1979, 3, 435–443. Flörke, M., Schneider, C., McDonald, R.I., 2018. Water competition between cities and agriculture driven by climate change and urban growth. Nature Sustainability, 1(1), 51–58. DOI:10.1038/s41893-017-0006-8. Hedberg, T., 2018. The unintended consequences of dams and reservoirs. Press release: Uppsala University, Sweden. Retrieved from https://www.uu.se/en/press/press-release/?id=4512&area=3%2C8&typ=pm&lang=en Hemati, A., Rippy, M.A., Grant, S.B., Davis, K., Feldman, D., 2016. Deconstructing Demand: The Anthropogenic and Climatic Drivers of Urban Water Consumption. Environmental Science & Technology, 50(23), 12557– 12566. DOI:10.1021/acs.est.6b02938 Hutton, N.S., Tobin, G.A., Montz, B.E., 2018. The levee effect revisited: Processes and policies enabling development in Yuba County, California. Journal of Flood Risk Management, 12(3), e12469. DOI:10.1111/jfr3.12469. ISSN 1753-318X Khilchevskyi, V., Grebin, V., Dubniak, S., Zabokrytska, M., Bolbot, H., 2021. Large and small reservoirs of Ukraine. Journal of Water and Land Development. 2021. No. 49 (IV–VI). Khilchevskyi, V., Karamushka, V., 2021. Global Water Resources: Distribution and Demand. In: Leal Filho, W., Azul, A.M., Brandli, L., Lange Salvia, A., Wall, T. (eds) Clean Water and Sanitation. Encyclopedia of the UN Sustainable Development Goals. Springer. DOI: 10.1007/978-3-319-70061- 8_101-1 Konar, M., Garcia, M., Sanderson, M.R., Yu, D.J., Sivapalan, M., 2019. Expanding the scope and foundation of sociohydrology as the science of coupled human‐water systems. Water Resources Research, 55, 1-14. DOI:10.1029/2018WR024088 Koutsoyiannis, D., 2011. Review Report of “Socio-Hydrology: A New Science of People and Water”; National Technical University of Athens: Athens, Greece.. Retrieved from http://www.itia.ntua.gr/en/docinfo/1991/ Madani, K., Shafiee-Jood, M., 2020. Socio-Hydrology: A New Understanding to Unite or a New Science to Divide?. Water. 12, 1941, 1-26. DOI: 10.3390/w12071941 McCurley, K.L., Jawitz., J.W., 2017. Hyphenated hydrology: Interdisciplinary evolution of water resource science. Water Resources Research, 53, 2972–2982. DOI: 10.1002/2016WR019835 Nüsser, M., 2017. Socio-hydrology: A New Perspective on Mountain Waterscapes at the Nexus of Natural and Social Processes. Mountain Research and Development, 37(4), 518-520. DOI: 10.1659/MRD-JOURNAL- D-17-00101.1 Seidl, R., Barthel, R., 2017. Linking scientific disciplines: Hydrology and social sciences. Journal of Hydrology, 550, 441–452. DOI: 10.1016 / J.JHYDROL.2017.05.008 Shiau, J.T., 2003. Water Release Policy Effects on the Shortage Characteristics for the Shihmen Reservoir System during Droughts. Water Resources Management, 17(6), 463–480. DOI:10.1023/b:warm.0000004958.93250.8a. ISSN 0920-4741. Sivakumar, B., 2012. Socio-hydrology: Not a new science, but a recycled and re-worded hydrosociology. Hydrological Processes, 26, 3788–3790. Sivapalan, M., 2015. Debates – Perspectives on socio-hydrology: Changing water systems and the ”tyranny of small problems” – Socio- hydrology. Water Resources Research, (51)6, 4795–4805. DOI. 10.1002/ 2015WR017080 Sivapalan, M., Blöschl, G., 2015. Time scale interactions and the coevolution of humans and water. Water Resources Research.,51 (9), 6988– 7022. DOI:10.1002/2015WR017896 Sivapalan, M., Savenije, H., Blöschl, G., 2012. Socio-hydrology: A new science of people and water.. Hydrological Processes, 26 (8), 1270–1276. DOI: 10.1002/hyp.8426 Srinivasan, V., Lambin, E.F., Gorelick, S.M., Thompson, B.H., Rozelle, S., 2012. The nature and causes of the global water crisis: Syndromes from a meta-analysis of coupled human-water studies. Water Resources Research, 48 (10), W 10516. DOI:10.1029/2011WR011087 Su, Y., Kern, J.D., Denaro, S., Hill, J., Reed, P., Sun, Y., Cohen, J., Characklis, G.W., 2020. An open source model for quantifying risks in bulk electric power systems from spatially and temporally correlated hydrometeorological processes. Environmental Modelling and Software. 126. 1-12. DOI: 10.1016/j.envsoft.2020.104667 Sung, K., Jeong, H., Sangwan, N., Yu, D.J., 2018. Effects of flood control strategies on flood resilience under sociohydrological disturbances. Water Resources Research, 54, 2661–2680. DOI: 10.1002/2017WR021440 Viglione, A., Di Baldassarre, G., Brandimarte, L., Kuil, L., Carr, G., Salinas J.L., Scolobig, A., Blöschl. G., 2014. Insights from socio-hydrology modelling on dealing with flood risk – Roles of collective memory, risk-taking attitude and trust // Journal of Hydrology, 518, 71–82. DOI: 10.1016/j.jhydrol.2014.01.018 Vogel, R.M., Lall, U., Cai, X., Rajagopalan, B., Weiskel, P.K., Hooper, R.P. Matalas N.C., 2015. Hydrology: The interdisciplinary science of water. Water Resources Research, 51, 4409–4430. DOI: 10.1002/2015WR017049 Wesselink, A., Kooy, M., Warner, J., 2017. Socio-hydrology and hydrosocial analysis: toward dialogues across disciplines. Wiley Interdisciplinary Reviews. Water, 4 (2), e1196. DOI: 10.1002/wat2.1196 Xu, L., Gober, P., Wheater, H.S., Kajikawa, Y., 2018. Reframing socio- hydrological research to include a social science perspective. Journal of Hydrology, 563, 76–83. DOI: 10.1016/j.jhydrol.2018.05.061 Xu, Z., Yang, Z., Cai, X., Yin X., 2020. Modeling framework for reservoir capacity planning accounting for fish migration. Journal of Water Resources Planning and Management, 146. DOI: 10.1061/(ASCE)WR.1943- 5452.0001170
Keywords: соціогідрологія; система “людина – вода”; соціогідрологічне моделювання; інтегроване управління водними ресурсами; водосховища; гідрологія; socio-hydrology; human-water system; socio-hydrological modeling; integrated water resources management; reservoirs; hydrology